Hepatitis B vaccine effectiveness in the face of global HBV genotype diversity. (December 2011) - Cassidy, Adrian; Mossman, Sally; Olivieri, Antonio; Ridder, Marc De; Leroux-Roels, Geert
Recombinant hepatitis B vaccines are of the A2 genotype; one of ten known genotypes whose distribution varies globally. Reports of rare HBV infections in blood donors with an imbalance of non-A2 genotype HBV in vaccinated subjects have raised questions about the cross-protection afforded by HBV-A2 vaccines. Infections in HBV vaccinees were asymptomatic and transient, indicating that vaccination prevented clinical disease. Preclinical data demonstrate cross-reactivity and cross-protection by A2 vaccines against non-A2 HBV genotypes. Substantial improvements in HBV control have been demonstrated in countries with diverse genotype distribution that have introduced universal childhood HBV vaccination programs. Available data show that current HBV-A2 vaccines are highly effective in preventing infections and clinical disease caused by all known HBV genotypes.